VALUATION OF RESISTANCE TO PLASMODIOPHORA BRASSICAE OF HYBRID COMBINATIONS OF WHITE HEAD CABBAGE DEVELOPED BASED ON DOUBLED HAPLOID LINES - A. I. Mineikina; A. A. Ushakov; L. L. Bondareva (Овощи России)
Plasmodiophora brassicae Wor. is the one of the causative agent of disease of the family of Brassicaceae, that results in decrease of white head cabbage yield up to 10-60%. The aim of the work was the study of genetic variability of doubled haploid lines of white head cabbage obtained by the isolated microspore culture in vitro aimed at selection of the lines resistant to P. Brassicae and development of resistant hybrids. The doubled haploid lines of white head cabbage were evaluated for resistance to Plasmodiophora brassicae using the method of inoculation of seedlings by pathogen in the control condition of the chamber room. As a result of assessment, the high disease distribution among doubled haploid lines was found (25- 100%), but disease development was not higher than 68%. The score of infestation was 0.5-3.3, that was comparable with the standard (3.5). The plants of the lines 3-3-3 did not exhibit any symptoms of disease that can indicate of efficiency of its gene resistance or pathogen heterogeneity. The lines with high resistance to P. brassicae were used as a parental lines for development of F1 hybrids. Using the top-crossing method the forty-two hybrid combinations were developed based on self-incompatibility. These hybrid combinations were analyzed for clubroot resistance in the field conditions on an artificial infectious background in Moscow region. Based on the data of two-year experiments, all tested hybrid combinations were divided into the groups of relatively tolerant (52.4%) and susceptible (45.2%) genotypes. Only one hybrid combination developed with line 3-3-3 has proved to be tolerant. The score of infestation of hybrid combinations varied from 0 to 1.8. The score of infestation of the standard was 2.5. The disease distribution reached 80% but disease development varied from 0 to 25%.